Vattenvård vid slutavverkning : före och efter vattenvårdsutbildning på Stora Enso Skog, distrikt Siljan - Sundin, Sara (SLU/School for Forest Management, 2008)
In 2006, Stora Enso Skog implemented an education program in water management for harvester operators, timber purchasers, cut block planners and supervisors. The focus of the program was creating stream crossings with minimal harm to the stream and the surrounding riparian area. This main purpose of this study was to determine the difference in work procedures before and after participating in the program. The methodology consisted of field studies and interviews with harvester operators and their supervisors. The field study looked at how the streams had been crossed concerning the number of crossings, visible damage to the stream and/or the riparian area made by the machines. Biological parameters such as the width and dept of the stream and amount of large woody debris in the stream were also measured. The field result from 30 harvesting sites showed no significant difference between sites that had been harvested before or after the education program. But the harvester operators and their supervisors experienced an increased concern for watersheds after the educational program. The harvester operators liked the fact that the program both had practical and theoretical parts and that there was plenty of time for discussions. Before participating in the program they were less concerned with small streams, now they felt that all streams were important. The harvester operators felt that planning was important in order for them to do a good job, both concerning site planning and at harvesting time. Many of the teams and the supervisors would like to have portable bridges to carry with them to each site. Feedback between harvester teams, site planners and supervisors were also mentioned as a factor of success. Economical compensation is a prerequisite in order to make the harvester teams willing to put in the extra time needed for building bridges and for creating good stream crossings.